Exploring education and training needs among the palliative care workforce. Issue 2 (13th February 2013) - Ingleton, Christine; Gardiner, Clare; Seymour, Jane E; Richards, Naomi; Gott, Merryn
Abstract : Objectives: Education and training are seen as 'absolutely essential parts of providing palliative care'. As part of a larger study to explore the extent of palliative care need in two acute hospital settings, we report the perceptions of healthcare professionals regarding their training and educational needs. Methods: In Phase 1, we undertook eight focus groups and four individual interviews with 58 health professionals from general practice, specialist palliative care and acute hospitals, exploring perceived education and training priorities. Phase 2 of the study involved a survey of palliative care need at two hospitals in England. Hospital based doctors and nurses completed questionnaires to identify patients with palliative care needs and to respond to questions about their training and education needs. Results: Various barriers exist to the provision and management of palliative care, not least a need for more education and training. Focus group participants felt they were not adequately trained to address prognosis and goals of care with patients and their families. In Phase 2 of the study, 171 nursing staff and 81 medical staff completed the questionnaire and two-thirds of our sample felt they required additional training in palliative care. Conclusions: Although important, the use of standardised care pathways alongside the provision of education and training for healthcare professionals alone will not improve quality of care. More work is needed to examine and clarify the interplay of: behaviour change, setting, the 'cure' orientation approach, type of health professional and nature of any educational intervention in order to effect sustained behavioural change.